Implementation Of Good Corporate Governance (GCG) In Palm Oil Plantation Companies In Indonesia (Literature Review) - Akbar, Ayip Ridwan; Sendjaja, Theodorus; Yanuar Arifin, Asep; Kusuma, Athalia (Universitas Indo Global Mandiri, 2024)
Palm oil plantations are one of the important sectors in the Indonesian economy that remained strong during the global financial crisis and contributed greatly to the country's foreign exchange. The world's largest exporters of palm oil are Indonesia and Malaysia with the largest contributions of 26.60 million tons and 15.40 million tons respectively in 2022. Companies are trying to improve the implementation of Good Corporate Governance (GCG) to comply with regulations and improve the quality of management in a sustainable manner. The purpose of this study is to review the literature on the implementation of GCG in palm oil plantation companies, its impact on company performance, and obstacles in its implementation, using a qualitative literature study method. The results of the study indicate that the implementation of GCG in companies such as PT Bumitama Gunajaya Agro, PT. PP. London Sumatera Indonesia Tbk, and PT Agro Sinergi Nusantara has succeeded in meeting the principles of GCG and increasing Return on Assets (ROA). However, there are obstacles such as lack of management commitment, limited resources, unsupportive corporate culture, and external pressures and conflicts of interest. By overcoming these obstacles, it is hoped that companies in the palm oil plantation sub-sector can be more effective in implementing GCG, thereby improving their financial performance and business sustainability.